MENINGKATKAN KECAKAPAN KEWARGANEGARAAN (CIVIC SKILL) MELALUI PEMBELAJARAN PKN BERBASIS PROJECT CITIZEN (STUDI KUASI EKSPERIMEN DI SMK YPT BANJARMASIN) - Norlaili Hidayati (JURNAL SOCIUS, 2013)
Project Citizen is a learning model that able to improve the skills of citizenship education including intellectual skills and participation skills. Project Citizen is a portofolio-based learning model. This study uses a quantitative approach. The method used is a quasi experimental design with "randomeized control group pre-test post-test design". In this design the samples were divided into two groups: one group with another group of experimental and one control group. The results showed a significant improvement in intellectual skills and the skills of participation in the experimental class than the control class. The data shows that students respond were better civics lesson using the model citizen of the project than using a conventional model. Based on this study, the recommendation addressed to teachers in order to practice learning civics project model citizen because it can increase the citizenship skill students that include intellectual skills and participation skills.Key words: Project citizen, citizenship education, citizenship skills